Faktor-Faktor yang Mempengaruhi Self-Care pada Pasien Heart Failure - Tuti Pahria; Tobi Pitora; Eka Afirmasari (FORIKES, 2022)
Heart failure describes a complex clinical syndrome when the heart is unable to maintain sufficient cardiac output to meet the body's metabolic needs, which carries a high risk of death. This study aims to analyze the factors that influence self-care in patients with heart failure. This study was a literature review using 5 databases, namely Proquest, PubMed, Science Direct, Willey, and CINAHL which were published between 2011 and 2021. Furthermore, 11 articles that met the criteria were obtained. The results of the review show that in an effort to implement self-care in individuals with heart failure, a comprehensive assessment is needed so that factors that can influence the implementation of self-care can be identified. The application of good self-care can help individuals to prevent complications. Factors that could influence the application of self-care to individuals were knowledge, experience, skills, motivation, habits, functional and cognitive abilities, self-efficacy, support systems, and cultural values. It was concluded that the implementation of self-care in individuals with heart failure was influenced by several factors including knowledge, social support, self-efficacy and physical activity.Keywords: social support; heart failure; confidence; knowledge; self-care ABSTRAK Heart failure menggambarkan gambaran sindroma klinis yang kompleks ketika jantung tidak mampu mempertahankan curah jantung yang cukup untuk memenuhi kebutuhan metabolisme tubuh, yang memiliki resiko kematian yang tinggi. Penelitian ini bertujuan untuk menganalisis faktor-faktor yang mempengaruhi self-care pada pasien dengan heart failure. Studi ini merupakan literature review menggunakan 5 database yaitu Proquest, PubMed, Science Direct, Willey, dan CINAHL yang diterbitkan dalam rentang tahun 2011 sampai dengan 2021. Selanjutnya didapatkan 11 artikel yang memenuhi kriteria. Hasil review menunjukkan bahwa dalam upaya penerapan self-care pada individu dengan heart failure diperlukan pengkajian secara komprehensif sehingga dapat diketahui faktor yang dapat mempengaruhi penerapan self-care. Penerapan self-care yang baik dapat membantu individu untuk mencegah terjadinya komplikasi. Faktor yang dapat mempengaruhi penerapan self-care pada individu adalah pengetahuan, pengalaman, skill, motivasi, kebiasaan, kemampuan fungsional dan kognitif, self-efficacy, support system, serta nilai budaya. Disimpulkan bahwa penerapan self-care pada individu dengan heart failure dipengaruhi oleh beberapa faktor antara lain pengetahuan, dukungan sosial, self-efficacy dan physical activity.Kata kunci: dukungan sosial; heart failure; kepercayaan diri; pengetahuan; self-care